Editorial - Editor (Dev Sanskriti: Interdisciplinary International Journal, 2023)
Dev Sanskriti Interdisciplinary International Journal brings together the studies of interdisciplinary domains, science and spirituality, Indic and modem streams of learning is again presented from Dev Sanrkriti Vishwavidyalaya. The current issue of the DSIIJ is concentrated on the study of the integration of Psychology and Veda. This integration is motivated by the complete integration of the immense but fairly contemporary view of the mind, emotions and psyche and how this performs in our lives. Prespective of the currect issue explains the Integrating Psychotherapy and Vedic principles which teaches us how to rediscover critical knowledge and awareness of the natural forces and rhythms that complement and strengthen our human experience, through the understanding of the psyche and what our inner experiences are and also involving practical daily activities of yoga with thorough attention to our total environment to bring about radical changes in our mental outlook and in physical health fulfilling the unique vision of the groundbreaking scholar and great visionary, Pandit Shriram Sharma Acharaya, to mould its students into noble and enlightened human beings; selfless, warm-hearted, compassionate and kind individuals. Trough our Journal, we present you a collection of research papers and studies that addresses and expresses the new dimensions of interdisciplinary research.